KEMAMPUAN BERPIKIR TINGKAT TINGGI : ANALISIS FILOSOFIS, PEDAGOGIS, PSIKOLOGI, DAN SOSIAL - M. Kholis Amrullah (Nizham Journal of Islamic Studies, 2022)
Some assumptions regarding high-level thinking are something that allows it to be obtained. In fact, this ability cannot be obtained, but must be trained and applied repeatedly. In this article, the ability to think at a high level is connected with several approaches, namely philosophical, pedagogical, psychological, and social. The culmination of higher-order thinking skills is being able to communicate well with society. this preposition is based on the findings of an analysis that leads to the ability of humans to classify and overcome problems. Psychologically, the ability to think high helps humans in determining the right decisions in taking actions.